Surgery 101 Podcast: Episodes 101-110 - Jonathan White; Kamran Fathimani; Tammy Morris; Keith Rourke; Jeffrey Pugh; Mitchell P. Wilson; Parveen Boora; Mark Joffe; Shannon Erichsen; Katrina Pederson; Jenni Marshall (Association of American Medical Colleges, 2013)
Abstract This resource is a series of podcasts intended to serve as brief introductions to and reviews of surgical topics for medical students. The aim was to cover a single topic in 15-20 minutes so that learners could quickly grasp the basic concepts relating to common surgical problems. Learning objectives are provided for each episode; episodes are divided into chapters and conclude with several key points to summarize the topic. This module contains topics/episodes on how to read an abdominal X-ray, how to avoid fainting in the operating room, pelvic pain, urinary incontinence, increased intracranial pressure, hydrocephalus, peptic ulcer disease, hand hygiene, and anal fistula. Surgery 101 has been produced since October 2008; it was created by Dr. Parveen Boora and Dr. Jonathan White and is currently produced by the Undergrad Surgery Mobile Podcasting Studio Team with the assistance of the members of the Surgery Department at the University of Alberta.